Uma experiência de cibereducação para o letramento digital - Almeida, Regiceli Bento [UNESP] (2015)
The objective of this paper is to present the possibilities of using social media, Facebook, to be more specific, as a pedagogical and didactic tool in Portuguese language classes for the 9th grade to develop reading and writing skills by reading and writing different text/digital genres that are found in this media. In order to do so, firstly we researched about Educational technologies by surveying and reflecting about the pedagogical uses of social media. Activities were developed with 9th grade students in a state school inland São Paulo state who are native computer users dealing well with technology, but still in formal education and need to take part in social practices. Several researches in Education point out that there are difficulties towards reading and writing with basic education students. However thanks to digital spaces, students have never read and written so much. So, we cannot deny the need of using technology in schooling. By using it, we intend to help students to become citizens, to build new knowledge and hence, to broad horizons by forming multi literate students